Práticas colaborativas de criação de conhecimento para a inclusão financeira: um estudo em redes de cooperativas de crédito - Silva, Renan Nunes da (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation addresses the theme of collaborative practices of knowledge creation in credit cooperative networks. Small businesses are important players in world economies, whether in developed or developing countries. However, historically this segment presents difficulties in obtaining access to formal financial products and services in the traditional banking market. As an alternative to the financial inclusion of small businesses, credit cooperatives emerge that, acting in networks, carry out practices that generate knowledge assets relevant to the financial inclusion of these companies. The study aims to identify the main collaborative practices of knowledge creation, carried out in networks of credit cooperatives, and how they mobilize different types of knowledge capable of generating assets that foster financial inclusion. In order to investigate and deepen the problem, an empirical research was carried out on three Credit Cooperative Networks aimed at creating knowledge for the financial inclusion of small businesses located in the states of Mato Grosso, Paraná and Minas Gerais, as well as the national coordination of Networks, which is carried out by the Brazilian Micro and Small Business Support Service (Sebrae). The results allow a description of the main practices and the context necessary for the accomplishment of these collaborative practices to be related to the promotion of financial inclusion of small businesses.
Keywords: Práticas colaborativas; Criação de conhecimento; Ativos de conhecimento; Inclusão financeira; Redes de cooperativas de crédito; Collaborative practices; Creation of knowledge; Knowledge assets; Financial inclusion; Cooperative credit networks; ACCNPQ::Ciências Sociais Aplicadas::Administração